Qingjin Yiqi granules for post‐COVID‐19 condition: A randomized clinical trial. Issue 1 (13th April 2022) - Pang, Wentai; Yang, Fengwen; Zhao, Yubin; Dai, Erhei; Feng, Jihong; Huang, Yuhong; Guo, Yongming; Zhou, Shengyuan; Huang, Ming; Zheng, Wenke; Ma, Jiang; Li, Hong; et al.
Abstract: Objective: To evaluate the effectiveness and safety of Qingjin Yiqi granules (QJYQ) on post‐COVID‐19 condition (PCC). Method: Patients who met the inclusion criteria were randomly assigned to two groups, the QJYQ group received QJYQ combined with standard rehabilitation treatments (SRTs) and the control group only received SRTs. The treatment course was 14 days. The primary outcomes were modified Medical Research Council (mMRC) scale and Borg scale, while the secondary outcomes included symptoms score and 6‐minute walking distance (6MWD). The safety outcome was the incidence of adverse events. Results: A total of 388 patients with PCC were enrolled and randomly assigned to the QJYQ group ( n = 194) and the control group ( n = 194). Compared to the controls, the mMRC scale was improved in the QJYQ group, which was better than that of the control group [β (95%CI): –0.626 (–1.101, –0.151), p = 0.010]. A significant improvement in Borg scale was also observed in the QJYQ group compared to the control group [β (95%CI): –0.395(–0.744, –0.046), p = 0.026]. There was no statistically significant difference in symptoms score and 6MWD between the two groups ( p = 0.293, p = 0.724). No treatment‐related adverse events were observed in either group. Conclusions: QJYQ can bring benefits to patients with PCC, mainly in the improvement of breathlessness and fatigue.